2009
DOI: 10.1105/tpc.108.060434
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior ofArabidopsiseIF4A-III, Putative Core Protein of Exon Junction Complex: Fast Relocation to Nucleolus and Splicing Speckles under Hypoxia

Abstract: Here, we identify the Arabidopsis thaliana ortholog of the mammalian DEAD box helicase, eIF4A-III, the putative anchor protein of exon junction complex (EJC) on mRNA. Arabidopsis eIF4A-III interacts with an ortholog of the core EJC component, ALY/Ref, and colocalizes with other EJC components, such as Mago, Y14, and RNPS1, suggesting a similar function in EJC assembly to animal eIF4A-III. A green fluorescent protein (GFP)-eIF4A-III fusion protein showed localization to several subnuclear domains: to the nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
89
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 50 publications
6
89
1
4
Order By: Relevance
“…The localization of CML38 to both the nucleus and cytosol suggests that this protein may also be associated with RBP47 mRNPs in both locations. Consistent with this, the Arabidopsis ortholog of the mammalian DEAD box helicase (Table I), eIF4A-III, and the putative anchor protein of the exon junction complex (Koroleva et al, 2009;Supplemental Table S1, sheet 3), are among the CML38-interacting proteins detected by MS analysis. In addition, CML38 immunoprecipitates also contained proteins associated with the nuclear U3 snoRNP complex (small and large ribosomal subunit proteins, TCH-1 chaperones, and the 26S proteasome regulatory subunit S2; Table I; Samaha et al, 2010), which is involved in ribosome biogenesis, suggesting another potential function in RNA metabolism.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The localization of CML38 to both the nucleus and cytosol suggests that this protein may also be associated with RBP47 mRNPs in both locations. Consistent with this, the Arabidopsis ortholog of the mammalian DEAD box helicase (Table I), eIF4A-III, and the putative anchor protein of the exon junction complex (Koroleva et al, 2009;Supplemental Table S1, sheet 3), are among the CML38-interacting proteins detected by MS analysis. In addition, CML38 immunoprecipitates also contained proteins associated with the nuclear U3 snoRNP complex (small and large ribosomal subunit proteins, TCH-1 chaperones, and the 26S proteasome regulatory subunit S2; Table I; Samaha et al, 2010), which is involved in ribosome biogenesis, suggesting another potential function in RNA metabolism.…”
Section: Discussionmentioning
confidence: 55%
“…Similar to previous studies of time-resolved SG disassembly in plant tissues recovering from hypoxia (Sorenson and BaileySerres, 2014) and related heat stress (Gutierrez-Beltran et al, 2015), the CML38 foci disassemble upon reoxygenation. Second, MS analysis of immunoprecipitates of CML38 from hypoxic root samples reveals the presence of established SG-associated proteins, including poly(A)-binding protein (Kedersha et al, 2002;Kimball et al, 2003;Sorenson and Bailey-Serres, 2014), eukaryotic initiation factors (Li et al, 2010), eukaryotic elongation factors (HafrĂ©n et al, 2013), RNA helicase (Koroleva et al, 2009), small ribosomal subunit proteins (Kedersha et al, 2002;Sorenson and Bailey-Serres, 2014), and others (Mazroui et al, 2007;Buchan et al, 2013;Yan et al, 2014, GutierrezBeltran et al, 2015. Third, coexpression of the core SG-nucleating RNA-binding protein RBP47 (Weber et al, 2008) with CML38 shows that, under hypoxia conditions, the two proteins colocalize to cytosolic granules.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dehydration stress and heat stress increase the production of transcripts encoding the full-length SR45a protein, an atypical SR-like protein, relative to other splice variants (Gulledge et al, 2012). Furthermore, stress signals affect both the phosphorylation status and subcellular localization of Arabidopsis SR and splicingrelated proteins (Ali et al, 2003;Tillemans et al, 2005Tillemans et al, , 2006de la Fuente van Bentem et al, 2008;Koroleva et al, 2009;Rausin et al, 2010). Phosphorylation may affect the function of SF protein isoforms.…”
Section: As Of Sfs In Response To Abiotic Stressmentioning
confidence: 99%
“…In plants, DEADbox RNA helicases have been associated with diverse molecular functions such as siRNA-mediated gene silencing, premRNA splicing, chloroplast/mitochondrial intron splicing, nonsense-mediated mRNA decay, mRNA export, ribosome biogenesis and exon-junction complex functions. [11][12][13][14][15][16][17][18][19][20][21][22] Furthermore, it has been shown that these helicases play roles in Keywords: abiotic stress, Arabidopsis thaliana, DEAD-box RNA helicases, epigenetic gene silencing, nucleolus, RNAdirected DNA methylation Abbreviations: ABA, abscisic acid; STRS, STRESS RESPONSE SUPPRESSOR; RdDM, RNA-directed DNA methylation. various biological processes including abiotic stress responses.…”
mentioning
confidence: 99%
“…various biological processes including abiotic stress responses. 6,12,15,19,[23][24][25][26][27][28][29] To further explore the function of the STRS DEAD-box RNA helicases in regulating abiotic stress-responsive gene expression, we examined STRS sub-cellular localization.…”
mentioning
confidence: 99%